2001
DOI: 10.1152/ajpcell.2001.280.5.c1076
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nucleoside transport systems in cultured rat epididymal epithelium

Abstract: The nucleoside transport systems in cultured epididymal epithelium were characterized and found to be similar between the proximal (caput and corpus) and distal (cauda) regions of the epididymis. Functional studies revealed that 70% of the total nucleoside uptake was Na(+) dependent, while 30% was Na(+) independent. The Na(+)-independent nucleoside transport was mediated by both the equilibrative nitrobenzylthioinosine (NBMPR)-sensitive system (40%) and the NBMPR-insensitive system (60%), which was supported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Time-and temperature-dependent uridine uptake was observed, and an excess of unlabeled uridine and NBMPR inhibited this uptake (data not shown), suggesting that the nucleoside transporters take up essential nucleosides for spermatogenesis. In primary-cultured rat epididymal epithelial cells, ENT1, ENT2, and CNT2 are expressed and sodium-dependent transporter CNT2 mainly mediates uridine uptake (Leung et al, 2001). Thus, Sertoli cells and epididymal cells appear to have in common CNT2, but the contribution of other nucleoside transporters may be different between these two types of cells, although both of these cells should contribute differentiation and maturation of spermatogenic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-and temperature-dependent uridine uptake was observed, and an excess of unlabeled uridine and NBMPR inhibited this uptake (data not shown), suggesting that the nucleoside transporters take up essential nucleosides for spermatogenesis. In primary-cultured rat epididymal epithelial cells, ENT1, ENT2, and CNT2 are expressed and sodium-dependent transporter CNT2 mainly mediates uridine uptake (Leung et al, 2001). Thus, Sertoli cells and epididymal cells appear to have in common CNT2, but the contribution of other nucleoside transporters may be different between these two types of cells, although both of these cells should contribute differentiation and maturation of spermatogenic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine is related to the acquisition of motility of sperm (Aitken et al, 1986;Vijayaraghavan and Hoskins, 1986), and nucleoside transport systems were characterized in rat epididymis epithelial cells (Leung et al, 2001). However, there is no information about nucleoside transport systems at the BTB, which is formed mainly by Sertoli cells.…”
mentioning
confidence: 99%
“…Studies investigating epididymal drug transport are limited, but one study revealed that ENT1, ENT2, and CNT2 are present in the epididymis (Leung et al, 2001). Without knowing the localization of these transporters, it is difficult to speculate on their potential impact on drug transport.…”
Section: Ent1 Responsible For Nucleoside Uptake Into Sertoli Cellsmentioning
confidence: 99%
“…Epididymal epithelial cells were isolated from 5-week-old Sprague-Dawley rats (Saitama Experimental Animal Supply Co. Ltd, Saitama, Japan) according to the method reported previously (Kierszenbaum et al 1981, Leung et al 2001. To minimize contamination of non-epithelial cells and inhibition of attachment of epithelial cells to culture dishes by spermatozoa, we used immature rats, which do not contain spermatozoa (Kierszenbaum et al 1981, Leung et al 2001.…”
Section: Preparation and Primary Culture Of Rat Epididymal Epithelialmentioning
confidence: 99%
“…To minimize contamination of non-epithelial cells and inhibition of attachment of epithelial cells to culture dishes by spermatozoa, we used immature rats, which do not contain spermatozoa (Kierszenbaum et al 1981, Leung et al 2001. Briefly, epididymides were dissected out and minced into small fragments.…”
Section: Preparation and Primary Culture Of Rat Epididymal Epithelialmentioning
confidence: 99%